PERANCANGAN PENGATURAN SISTEM TRAFFIC LIGHT BERDASARKAN JUMLAH KENDARAAN DENGAN MENGGUNAKAN CCTV DINAMIS - Florentinus Budi Setiawan; Erdhi Widyarto Nugroho; Yulianto Tejo Putranto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2010)
Intelligent Traffic System (ITS) implementation as an integrated control system needs some up-to-date data and many detectors for supporting system. Some research use the static CCTV camera to detect traffic density, vehicle speed and vehicle quantity. But there is no method for detecting the dynamic area with dynamic CCTV. The ain of the research is design of controlled traffic light system based on data of the vehicle quantity obtained by CCTV picture capture. The advantage of the research result is obtain the automatic and adaptive traffic light system based on the number of the vehicle. The recent ITS need some camera for some road that enter the crossing. The proposed systems only need one CCTV that dynamically supervising the number of vehicle. Conclusion of the research is that the camera can be used as traffic density detector. The picture that captured by this camera can be processed digitally, so that we obtain the traffic data. Data of the traffic condition are used as the reference for controlling the green lamp on each road on the cross. The other result is obtaining the prototype of hardware and software based on the research conclusion.